2013
DOI: 10.1152/ajpcell.00407.2012
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen governs Galβ1–3GalNAc epitope in human placenta

Abstract: It is becoming increasingly apparent that the dynamics of glycans reflect the physiological state of cells involved in several cell functions including growth, response to signal molecules, migration, as well as adhesion to, interaction with, and recognition of other cells. The presence of glycoconjugates in human placenta suggests their major role in maternal-fetal exchanges, intercellular adhesion, cellular metabolism, and villous vessel branching. Although several studies have described glycoconjugate distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…As a control and as expected, no band appears on the antibiotin membrane for the pristine MCF‐7 cells (Figure B). To further demonstrate protein site specificity, six glycoproteins, including three glycoproteins bearing experimentally confirmed terminal Gal/GalNAc (transferrin receptor, Hsp90 α,,, annexin II,,) (Supporting Information, Figure S8) and three regularly encountered glycoproteins (integrin α5, ENO1,, Hsp27) (Supporting Information, Figure S9), are purified with immunoprecipitation, and none of these glycoproteins are modified under LCM condition. As an additional control, MCF‐7 cells undergoing direct treatment with GO identifies multiple bands on the antibiotin membrane (Supporting Information, Figure S10), suggesting the occurrence of non‐selective modification.…”
Section: Methodsmentioning
confidence: 99%
“…As a control and as expected, no band appears on the antibiotin membrane for the pristine MCF‐7 cells (Figure B). To further demonstrate protein site specificity, six glycoproteins, including three glycoproteins bearing experimentally confirmed terminal Gal/GalNAc (transferrin receptor, Hsp90 α,,, annexin II,,) (Supporting Information, Figure S8) and three regularly encountered glycoproteins (integrin α5, ENO1,, Hsp27) (Supporting Information, Figure S9), are purified with immunoprecipitation, and none of these glycoproteins are modified under LCM condition. As an additional control, MCF‐7 cells undergoing direct treatment with GO identifies multiple bands on the antibiotin membrane (Supporting Information, Figure S10), suggesting the occurrence of non‐selective modification.…”
Section: Methodsmentioning
confidence: 99%
“…Reactive oxygen species and hypoxia (low oxygen environment) are key modulators of the cellular redox state (Adler et al, 1999). ROS and hypoxia also modulate Golgi-associated vesicular trafficking, protein sorting and glycosylation events (Regoeczi et al, 1991; Koike et al, 2004; Yin et al, 2006; Shirato et al, 2011; Ermini et al, 2013; Lehnus et al, 2013; Belo et al, 2015). Most often, this is thought to be mediated mainly by hypoxia-inducible factors (HIF-1-3) that regulate the expression of hundreds of genes, including a variety of proteins involved in glycosylation.…”
Section: Altered Golgi Homeostasis In Golgi Dysfunction and Diseasementioning
confidence: 99%
“…In addition to protein folding, hypoxia and ROS affect many other cellular pathways including transcription, translation, vesicular trafficking, pH homeostasis, energy metabolism, autophagy, proliferation and cell death, as well as tumor cell invasion and metastasis (11,27,139). Several recent studies have also shown that ROS and hypoxia not only impair Golgi-associated vesicular trafficking and protein sorting steps, but also alter glycosylation (10,40,186). Therefore, the Golgi is by no means different from any other organelle known to be affected by ROS and hypoxia.…”
Section: The Golgi Apparatus (Ga) Hypoxia and Rosmentioning
confidence: 99%